Self-diffusion coefficients obtained from proton-decoupled carbon-13 spectra for analyzing a mixture of terpenes - Yemloul, Mehdi (Magnetic resonance in chemistry : MRC, 2009)
In the limit of sufficient sensitivity, natural abundance 13C offers a much better spectral resolution than proton NMR. This is due to an important chemical shift range and to proton-decoupling conditions that yield one peak per carbon with practically no overlap. However, pulsed gradient spin echo experiments, which lead to the diffusion coefficient associated with each peak, have scarcely been employed. In this article, we present and compare different ways to access this quantity and we have effectively verified that, without any precaution, diffusion coefficients cannot be properly determined from standard procedures. The cause of such a failure is decoupling during the gradient pulses. We have used a very simple remedy that proved to be very successful on a model mixture of three monoterpenes and that appears as being of general applicability